Eksplorasi kreativitas matematis: Menganalisis pemahaman pola bilangan siswa SMP - Pebriana, Dian; Imami, Adi Ihsan (IKIP Siliwangi, 2024)
The aim of this research is to analyze and determine the mathematical creative thinking abilities of junior high school students in number pattern material. The method applied in this research is a descriptive method in qualitative research. The subject of this research was class VIII and a sample of 20 students were selected using purposive sampling at one of the junior high schools in Karawang Regency for the 2022/2023 school year. This research was carried out with a test instrument, namely in the form of questions consisting of 3 questions and each question consisted of indicators of fluency, flexibility and originality. The analysis techniques used are data reduction, data presentation, and drawing conclusions. The research findings show that there are 4 people with mathematical creative thinking abilities with a percentage of 20% in the high category, 10 people with a percentage of 50% in the medium category, and 6 people with a percentage of 30% in the low category. The results of the research show that the average in the medium category is that the high category is able to master all the indicators, the medium category is only able to master the fluency and flexibility indicators but the authenticity indicator is less mastered, and the low category is less able to master the third indicator.